Pour un Slow Urbanism - Joëlle Forest (VertigO)
Some fifty years ago the question of durability made its spectacular start in urban discourse. It is currently the inescapable reference in urban policies. However designing a sustainable city has given rise to fierce controversies. In this paper we will focus on the disjunction between long and present time. According to author, because of the urgency of a situation which requires immediate solutions, this disjunction is typical of a modus operandi lacking in reflexivity. Thus we suggest substituting slow urbanism to this emergency urbanism which favors reproduction to the detriment of innovation.